Performance Comparison and Seo Optimization Between Laravel Blade and Laravel Inertia in The Development of The Muncak.Id Website in Indonesia - Tempariyawan, Maulana Hafez Ahyatara; Akbar, Mohammad Irham; Nofiyati, Nofiyati; Waluyo, Sugeng (Informatika, Universitas Jenderal Soedirman, 2025)
Climbing mountains in Indonesia requires careful preparation, especially in understanding safe hiking routes and related information. A hiking route information website serves as a practical solution for hikers to access data easily and quickly. This study compares the performance and SEO optimization between Laravel Blade and Laravel Inertia in the development of the muncak.id website, which provides information on mountain hiking routes. The performance indicator tested is execution time, measured using Laravel Dusk. One of the test results for the hiking route access feature shows that Laravel Inertia Vue.js has an average execution time of 1.56 seconds, which is faster compared to Laravel Blade, which reached 3.89 seconds. In terms of SEO, both websites show good quality with no issues found. However, there are still opportunities for improvement in some areas marked as warnings and opportunities. Overall, Laravel Inertia with Vue.js proves superior in performance and consistency, as well as more effective in SEO optimization, making it the better choice for developing informative websites.